The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/10245332.2017.1333275
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics, molecular profile and outcomes of myeloid sarcoma: a single institution experience over 13 years

Abstract: Failure to achieve CR with induction therapy, and age >65 years are associated with poor outcomes in MS. Allogeneic stem-cell transplant in first remission appears to be the most effective modality for achieving long-term remissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 31 publications
3
59
1
Order By: Relevance
“…Kaur et al . studied 23 patients and found a significantly worse prognosis in patients older than 65 years . Interestingly, younger patients had a higher likelihood of having a ‘better prognosis’ tumour location, as previously discussed.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Kaur et al . studied 23 patients and found a significantly worse prognosis in patients older than 65 years . Interestingly, younger patients had a higher likelihood of having a ‘better prognosis’ tumour location, as previously discussed.…”
Section: Discussionsupporting
confidence: 59%
“…Kaur et al studied 23 patients and found a significantly worse prognosis in patients older than 65 years. 22 Interestingly, younger patients had a higher likelihood of having a 'better prognosis' tumour location, as previously discussed. Other studies failed to established a correlation between patient age and clinical outcomes in MS 6,23 (Table 2).…”
Section: Discussionmentioning
confidence: 58%
“…The neoplastic cells in MS often express precursor markers CD34 and/or CD117 together with granulocytic or monocytic markers such as MPO, CD13, CD33, CD68, and lysozyme. Different studies reported variable expression frequencies of MS for MPO (63–92%), CD13 (48%), CD33 (48–52%), CD68 (35–61%), and lysozyme (26–100%) [2, 57]. MS with monocytic differentiation can be particularly challenging to differentiate from histocytic sarcoma (HS) as both can express one or more monocytic antigens, such as CD68, CD163 and lysozyme.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, after allogenic bone marrow transplantation an increased incidence has been described 5. Very rarely, MS can occur in the absence of a systemic disease and predate onset of an underlying hematologic malignancy by months to years 6. Treatment options, including radiation and chemotherapy are based upon an early and accurate diagnosis is crucial 7.…”
Section: Introductionmentioning
confidence: 99%